AN OVERVIEW OF MACRONUTRIENT CONSUMPTION AND NUTRITIONAL STATUS OF HYPERTENSIVE PATIENTS WITH CARDIAC COMPLACATIONS HOSPITALIZED AT GENERAL HOSPITAL BANGLI - Ni Nengah Murniasih; Pande Putu Sri Sugiani; Gusti Ayu Dewi Kusumayanti (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2020)
The factor that causes hypertension is nutrient intake. This is because food has a significant role in increasing blood pressure. This study aims to describe the level of macro nutrient consumption and nutritional status of hypertensive patients with cardiac complications hospitalized at Bangli Hospital. This type of research is observational with a cross sectional approach. The population of this study was inpatients who were diagnosed with hypertension with cardiac complications inpatient care at Bangli Hospital, the study was conducted on samples aged ≥ 18 years. The results showed a low level of energy consumption (91.89%), less protein consumption (97.30%), less fat consumption level (67.57%), and less carbohydrate consumption (91.89%). Based on the results of normal nutritional status (54.05%), thin (5.41%), overweight (16.22%) while obesity (24.32%). The results of the level of energy consumption were less with normal nutritional status (52.94%), more weight (17.65%), and obesity (26.47%). The results of the level of protein consumption were lacking with normal nutritional status (51.35%), over weight (18.92%), and obesity (24.32%), the level of consumption of less fat with normal nutritional status (48.00%), more weight (24.00%), and obesity (28.00%), less carbohydrate consumption levels with normal nutritional status (55.88%), more weight (17.65%), and obesity (23.53) %). Keywords : Consumption level. Nutritional Status, Hypertensive Patients CardiacComplications.